The relationship among diabetes Self-Care, psychological adjustment, social support and glycemic control in the Lebanese population with type 2 diabetes mellitus - Sukkarieh-Haraty, Ola (2011)
Diabetes Mellitus (DM), is a chronic disease characterized by chronic hyperglycemia. In Lebanon, the prevalence rate of type 2 DM was 5.9% (N= 1982). The purpose of this study was to assess the relationship between diabetes self care, psychological adjustment and social support and glycemic control (A1C levels) among the Lebanese adults with diabetes mellitus. The study was descriptive correlational design with convenience sample of adults (N=140) diagnosed with type 2 DM recruited from two diabetes clinics. The participants completed a set of questionnaires: Summary of Diabetes Self-Care Activities (SDSCA) translated to Arabic, Social Support-Arabic version and Problem Areas In Diabetes (PAID) - Arabic version, and a demographic and physiological sheet. Test statistics used were reliability analysis and Mixed Models Theory with fixed and random effects presented in unadjusted and adjusted univariate models at p<0.05 level using Package for the Social Sciences (SPSS) version 18.0. Research question one was supported partially only when SDSCA subscales were categorized (beta= 0.66, SE=0.29, p-value=0.02). There were statistically significant relationships between PAID scores and glycemic control (B= 0.02, SE= 0.01, P-value= 0.036), thereby supporting Research questions 2. Social support scores was significantly associated with glycemic control (B= 0.02, SE= 0.01, p-value=0.01), yet in a positive direction as opposed to having negative significant relationship stated in research question 3. Age, Gender, type of treatment, problems associated with DM and BMI demonstrated statistical significant relationship with glycemic control (beta= 1.36, SE=0.35, p= 0.000; beta= 0.53, SE= 0.25, p= 0.037; beta= 0.99, SE= 0.31, P= 0.002; beta= -1.006, SE= 0.24, p=0.00; beta= 0.04, SE= 0.02. p= 0.033 respectively), thereby supporting some of the demographic and physiologic variables identified in research question 4. In research question 5, the aforementioned demographic and physiologic variables no longer demonstrated statistically significant association with A1C levels in the adjusted univariate model. In conclusion, the participants did not generally adhere to their diabetes self-care regimen except for medication regimen. Denial prevailed in light of the uncontrolled levels of A1C when emotional adjustment was examined. Finally, social support was positively associatedwith A1C levels, thereby inferring that as participants demonstrated uncontrolled levels of A1C, they got more social support from their network.